PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BAGIAN BIRO UMUM BP. BATAM - Syahrianto S; Dhenny Asmarazisa; Sriwati Sriwati (University of Riau Kepulauan, 2015)
The purpose of this study was to analyze the effect of compensation and motivation on the performance of the performance of employees in general Bureau Section BP. Batam, as well as to analyze the most dominant variable affecting performance. This research was conducted with a total population of 53 people. Retrieving data using the census, so that data is taken from the entire population. The variables in this study is divided into two, namely the independent and dependent variables. The independent variables consist of compensation and motivation and the dependent variable is the performance of employees. This research was conducted by examining the validity, reliability of the instrument, the classical assumption and hypothesis testing. The results using the t test showed that compensation and significant positive effect on employee performance and motivation effect is not positive and significant, while for F test showed that together compensation and motivation in a positive and significant impact on employee performance to the value F arithmetic.